Molten salt synthesis, visible and near-IR region spectral properties of europium or neodymium doped CoNb2O6 columbite niobate - BAŞAK, ALİ SADİ; EKMEKÇİ, METE KAAN; ERDEM, MURAT (ROYAL SOC CHEMISTRY, 2015)
Pure Nd3+- or Eu3+-doped CoNb2O6 powders have been prepared by a molten salt synthesis method using a Li2SO4-Na2SO4 or NaCl-KCl salt mixture as a flux at relatively low temperatures as compared to the solid state reaction method. X-ray diffraction patterns of pure CoNb2O6 samples indicated an orthorhombic single phase. For Eu3+-doped CoNb2O6 samples, the luminescence of Eu3+ was observed at 615 nm as red emission while the Nd3+ doped sample showed a typical emission at 1064 nm varying with the Eu3+ or Nd3+ doping concentrations. These luminescence characteristics of the doped samples may be attributed to the energy transfer between rare earth ions and CoO6 octahedral groups in the columbite structure.
Keywords: MICROWAVE DIELECTRIC-PROPERTIES; NONSTOICHIOMETRY; PHOSPHOR